Sarcopenia Is Associated with Quality of Life and Depression in Patients with Advanced Cancer. (21st September 2017) - Nipp, Ryan D.; Fuchs, Georg; El‐Jawahri, Areej; Mario, Julia; Troschel, Fabian M.; Greer, Joseph A.; Gallagher, Emily R.; Jackson, Vicki A.; Kambadakone, Avinash; Hong, Theodore S.; Temel, Jennifer S.; Fintelmann, Florian J.
Abstract : Background: Patients with advanced cancer often experience muscle wasting (sarcopenia), yet little is known about the characteristics associated with sarcopenia and the relationship between sarcopenia and patients' quality of life (QOL) and mood. Materials and Methods: As part of a randomized trial, we assessed baseline QOL (Functional Assessment of Cancer Therapy‐General [FACT‐G]) and mood (Hospital Anxiety and Depression Scale [HADS]) in patients within 8 weeks of diagnosis of incurable lung or gastrointestinal cancer, and prior to randomization. Using computed tomography scans collected as part of routine clinical care, we assessed sarcopenia at the level of the third lumbar vertebra with validated sex‐specific cutoffs. We used logistic regression to explore characteristics associated with presence of sarcopenia. To examine associations between sarcopenia, QOL and mood, we used linear regression, adjusted for patients' age, sex, marital status, education, and cancer type. Results: Of 237 participants (mean age = 64.41 ± 10.93 years), the majority were male (54.0%) and married (70.5%) and had lung cancer (56.5%). Over half had sarcopenia (55.3%). Older age (odds ratio [OR] = 1.05, p = .002) and education beyond high school (OR = 1.95, p = .047) were associated with greater likelihood of having sarcopenia, while female sex (OR = 0.25, p < .001) and higher body mass index (OR = 0.79, p < .001) correlated with lower likelihood of sarcopenia. Sarcopenia was associated with worse QOL (FACT‐G: B = −4.26, p = .048) and greater depression symptoms (HADS‐depression: B = −1.56, p = .005). Conclusion: Sarcopenia was highly prevalent among patients with newly diagnosed, incurable cancer. The associations of sarcopenia with worse QOL and depression symptoms highlight the need to address the issue of sarcopenia early in the course of illness. Implications for Practice: This study found that sarcopenia, assessed using computed tomography scans acquired as part of routine clinical care, is highly prevalent in patients with newly diagnosed, incurable cancer. Notably, patients with sarcopenia reported worse quality of life and greater depression symptoms than those without sarcopenia. These findings highlight the importance of addressing muscle loss early in the course of illness among patients with incurable cancer. In the future, investigators should expand upon these findings to develop strategies for assessing and treating sarcopenia while striving to enhance the quality of life and mood outcomes of patients with advanced cancer. Abstract : Cancer cachexia and sarcopenia can occur frequently in patients with advanced cancer, and may negatively affect treatment outcomes. This article highlights the importance of assessing sarcopenia and describes the relationship between sarcopenia and patients' quality of life in patients with newly diagnosed, incurable cancer.